Educational Intervention for Coping High Blood Pressure in Older Adults from Alamar - Juan Carlos Vázquez Pérez; Mariana Vasileva Anguelova (Universidad de las Ciencias Médicas de Cienfuegos, 2022)
Background: arterial hypertension constitutes one of the most prevalent medical-sanitary problems. Coping strategies and social support play an important role in the adaptation and management of this chronic disease. Objective: to evaluate the effectiveness of an educational intervention to promote coping with the disease in hypertensive older adults. Method: an intervention study was carried out between January and March 2020. The 253 hypertensive older adults from the family doctor's office 19, belonging to the Mario Escalona Reguera Teaching Polyclinic in Alamar, were the universe. The sample was non-probabilistic with 13 patients. Qualitative variables were analyzed: knowledge of the disease, lifestyles, self-care, coping, personological resources, emotional self-control, social support, communication and therapeutic adherence. The absolute frequencies and percentages of the qualitative variables were calculated. Results: with the application of the educational intervention program, the elderly managed to meet the objectives proposed in each session, acquired new knowledge and reflected on the need to modify lifestyles, exercise greater control over negative emotions, develop self-care and therapeutic adherence, to better cope with the disease. Conclusions: the educational intervention program was effective and had a favorable progress, while it modified the identified styles of coping with the disease. In this way, it was possible to modify in them the health problem.